5,11,17,23-Tetra-tert-butyl-25,26,27,28-tetrapropynyloxy-2,8,14,20-tetrathiacalix[4]arene - Li, Xiong (International Union of Crystallography, 2009)
The title compound [systematic name: 5,11,17,23-tetra-tert-butyl-25,26,27,28-tetrapropynyloxy-2,8,14,20-tetrathiacalix[4]arene], C(52)H(56)O(4)S(4), is an alkylated product bearing four propyne groups at the lower rim of a 5,11,17,23-tetra-tert-butyl-tetrathiacalix[4]arene. The molecule is located on a crystallographic twofold rotation axis, running through two S atoms and perpendicular to the long axis of the molecule. The four propyne groups, located in an alternate fashion above and below the mean plane of the four S atoms, are almost parallel to the calixarene long axis. The dihedral angle between the two crystallographically independent benzene rings is 86.77 (14)°. Two tert-butyl groups are disordered over two positions with site occupancies of 0.59 (2) and 0.41 (2).